Analysis Of Conservatism Accounting And Conflict Bondholders-Shareholder Against Quality Of Profit In Indonesia And Australia And Its Comparison - Elis Asri Munggaran; I Gede Sudi Adnyana (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2020)
This study aims to determine the effect of accounting conservatism and the conflict of bondholder-shareholders on the companies' earnings quality that list on the Indonesian Stock Exchange (IDX) and the Australian Securities Exchange (ASX). Besides, this study also aims to determine differences in Indonesia's earning quality level and Australia financial statements. The research method used is a quantitative statistical analysis using the classic assumption test, multiple regression analysis, T-test, and F test by a significance level of 5%. This study's independent variable (X) is accounting conservatism and shareholder bondholder conflict with the dependent variable (Y), earnings quality. The result of the analysis that has been done proves that partially and simultaneously, accounting conservatism has a significant effect on the earning quality in Indonesian and Australian companies. Meanwhile, in the study of the bondholder-shareholder conflict on earning quality shows that it does not affect achieving quality. But, simultaneously, it involves reaching quality in Indonesian and Australian companies. Meanwhile, based on descriptive statistical analysis, earnings quality in Australia is better than in Indonesia.